Impact of Hfq on the Intrinsic Drug Resistance of Salmonella Enterica Serovar Typhimurium - Hayashi-Nishino, Mitsuko; Fukushima, Aiko; Nishino, Kunihiko (Frontiers in Microbiology, 2012)
Salmonella enterica is an important enteric pathogen, and its various serovars cause both systemic and intestinal diseases in humans and domestic animals. The emergence of multidrug-resistant strains of Salmonella, leading to increased morbidity and mortality, has further complicated its management. Hfq is an RNA chaperon that mediates the binding of small RNAs to mRNA and assists in post-transcriptional gene regulation in bacteria. Although Hfq is related to important phenotypes including virulence in Salmonella, its role in the drug resistance of this organism is unknown. The aim of this study was to investigate the role of Hfq in intrinsic drug resistance of S. enterica serovar Typhimurium. hfq Mutant was susceptible to acriflavine. Although there is a relationship between the production of the AcrB multidrug efflux pump and Hfq in Escherichia coli, the deletion of the drug efflux acrB did not impair the effect of hfq deletion on Salmonella susceptibility. In contrast, the deletion of another drug efflux gene, smvA, impaired the effect of hfq deletion on acriflavine susceptibility. These results indicate that Hfq regulates the intrinsic drug resistance, and it may influence drug susceptibility by regulating SmvA in Salmonella.